Salt‐induced effects on microvascular function: A critical factor in hypertension mediated organ damage. Issue 6 (19th April 2019) - Marketou, Maria E.; Maragkoudakis, Spyros; Anastasiou, Ioannis; Nakou, Helen; Plataki, Marina; Vardas, Panos E.; Parthenakis, Fragiskos I.
Abstract: Salt has been linked very closely to the occurrence and complications of arterial hypertension. A large percentage of patients with essential hypertension are salt‐sensitive; that is, their blood pressure increases with increased salt intake and decreases with its reduction. For this reason, emphasis is placed on reducing salt intake to better regulate blood pressure. In day‐to‐day clinical practice this is viewed as mandatory for hypertensive patients who are judged to be salt‐sensitive. Previous studies have highlighted the negative effect of high‐salt diets on macrovascular function, which also affects blood pressure levels by increasing peripheral resistances. More recent studies provide a better overview of the pathophysiology of microvascular disorders and show that they are largely due to the overconsumption of salt. Microvascular lesions, which have a major impact on the functioning of vital organs, are often not well recognized in clinical practice and are not paid sufficient attention. In general, the damage caused by hypertension to the microvascular network is likely to be overlooked, while reversion of the damage is only rarely considered as a therapeutic target by the treating physician. The purpose of this review is to summarize the impact and the harmful consequences of increased salt consumption in the microvascular network, their significance and pathophysiology, and at the same time to place some emphasis on their treatment and reversion, mainly through diet.